Targeting complement in therapy - Kirschfink, Michael (Immunological reviews, 2001)
With increasing evidence that complement activation significantly contributes to the pathogenesis of a large number of inflammatory diseases, strategies that interfere with its deleterious action have become a major focus in pharmacological research. Endogenous soluble complement inhibitors (C1 inhibitor, recombinant soluble complement receptor 1, antibodies) blocking key proteins of the cascade reaction, neutralizing the action of the complement-derived anaphylatoxin C5a, or interfering with complement receptor 3 (CR3, CD18/11b)-mediated adhesion of inflammatory cells to the vascular endothelium have successfully been tested in various animal models over the past years. Promising results consequently led to clinical trials. Furthermore, incorporation of membrane-bound complement regulators (decay-accelerating factor (CD55), membrane co-factor protein (CD46), CD59) in transgenic animals has provided a major step forward in protecting xenografts from hyperacute rejection. At the same time, the poor contribution of complement to the antitumor response, which is caused by multiple resistance mechanisms that hamper the efficacy of antibody-based tumor therapy, is increasingly recognized and requires pharmacologic intervention. First attempts have now been made to interfere with the resistance mechanisms, thereby improving complement-mediated tumor cell destruction.
First published: 04 January 2002
Gesehen am 17.02.2021